2018
DOI: 10.1111/anae.14419
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics of children aged 2–17 years undergoing anaesthesia in Danish hospitals 2005–2015: a national observational study

Abstract: Provision of paediatric anaesthesia requires careful consideration of the child's cognitive state, unique body composition and physiology. In an observational cohort study, we describe the population characteristics and conduct of anaesthesia in children aged 2-17 years from 1 January 2005 to 31 December 2015. Children were identified from the Danish Anaesthesia Database. We recorded the following variables: age; sex; comorbidities; indications for anaesthesia; practice of anaesthesia; and complications. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, young age, medical history, and physical condition were shown to be the risk factors for serious critical events due to anaesthesia. Strøm et al [ 37 ] analyzed the Danish data bank for pediatric anaesthesia (aged 2–17 years), showing serious adverse events in less than 0.3% of cases [ 37 ]. However, submitting 10% of the children to the risk of anaesthesia solely for the purpose of imaging needs to be opposed to the risks of radiation exposure through CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…However, young age, medical history, and physical condition were shown to be the risk factors for serious critical events due to anaesthesia. Strøm et al [ 37 ] analyzed the Danish data bank for pediatric anaesthesia (aged 2–17 years), showing serious adverse events in less than 0.3% of cases [ 37 ]. However, submitting 10% of the children to the risk of anaesthesia solely for the purpose of imaging needs to be opposed to the risks of radiation exposure through CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, considering that the authors conducted a global review of perioperative cardiac arrests (Table 1), they did not include relevant and important articles found in the PubMed/Medline databases; examples include: Haché et al [ 21 ]; Jansen et al [ 22 ]; Kawashima et al [ 23 ]; Morita et al [ 24 ]; Strøm et al [ 25 ]; and Strøm et al [ 26 ].…”
mentioning
confidence: 99%
“…2 and 3 are the same); examples include Boonmak et al [ 27 ], Habre et al [ 28 ], Haché et al [ 21 ], Jansen et al [ 22 ], Kawashima et al [ 23 ], Morita et al [ 24 ], Strøm al. [ 25 ], and Strøm et al [ 26 ].…”
mentioning
confidence: 99%
“…Pediatric patients are unable to cooperate actively with anesthesia for their own reasons, resulting in pediatric surgery often requiring general anesthesia for surgical treatment [2] . However, the child's neurological function is in its developmental stage and inappropriate anesthesia will lead to neurological impairment, which will eventually affect long-term learning and memory function [3] . Studies have found that propofol causes apoptosis of neurons in the brain of animals during development, triggering cognitive dysfunction, but the specific mechanism of action is currently unknown [4] .…”
mentioning
confidence: 99%